Modification and elaboration of the original Smuts (2011) explanatory intention to quit structural model and empirical testing of the modified and elaborated Reitz model - Reitz, Islari (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.